On Taylor's scraping problem and flow of a Sisko fluid - Siddiqui, Abdul M.; Ansari, Ali R.; Ahmad, Ahmed; Ahmad, N. (Mathematical Modelling and Analysis, 2009)
The aim of the present investigation is to study the properties of a Sisko fluid flowing between two intersecting planes. The problem is similar to Taylor's scraping problem for a viscous fluid. We determine the solution of the complicated set of non‐linear partial differential equations describing the flow analytically. The analysis is carried out in detail reflecting the effects of varying the angle of the scraper on the flow. In addition, the tangential and normal stress are also computed. We also show the well known Taylor scraper problem as a special case.First published online: 14 Oct 2010